Inovasi Peningkatan Penjualan Minuman Kopi Aroma Kahuripan Menggunakan Metode Interpretive Structular Modelling (ISM) - Achmad Reza Adyatama (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Sales of coffee drinks from opening stands at bazaars and through social media have fluctuated. In November the target was exceeded. However, from December to April the target was not met. Based on these obstacles, there is a need for sales innovation that will increase sales of Aroma Kahuripan coffee drinks. This research uses qualitative research. After processing the data using ISM Professional software, the results showed that the obstacles that occurred in Aroma Kahuripan sales were unfriendly customer service and unattractive marketing. Apart from that, there are main actors in the sales process, namely marketing staff and baristas.